The Geomorphic Impact of Outburst Floods: Integrating Observations and Numerical Simulations of the 2000 Yigong Flood, Eastern Himalaya. Issue 5 (1st May 2019) - Turzewski, Michael D.; Huntington, Katharine W.; LeVeque, Randall J.
Abstract: Outburst floods in mountainous landscapes traverse complex topography and interact with the channel and valley walls, producing intense flow hydraulics that drive geomorphic change and impact people and infrastructure. Evidence of modern and ancient outburst floods is scattered around the eastern Himalaya, but hydraulics related to these geomorphic features are uncharacterized, limiting our understanding of the role of large floods in long‐term evolution of the region. Here we combine remote and field observations of the 2000 Yigong River landslide‐dam outburst flood with 2‐D numerical flood simulations using the software GeoClaw. Modeling results agree with field evidence to the extent that we judge the simulated hydraulics to be relevant to flood hazard and geomorphic investigations. Results show that the hydraulics of outburst floods through rugged topography differ from those expected for nonflood flows, in magnitude and in the spatial patterns of flow speed, direction, and shear stress. The flood produced sustained high bed shear stresses capable of plucking meter‐scale blocks immediately downstream of breach, in the steep Tsangpo Gorge, and in isolated locations associated with valley constrictions. Simulated shear stresses suggest that outburst floods deposited numerous kilometer‐scale boulder bars observed along the flood pathway, armoring the bed, increasing channel roughness, and inhibiting incision in locations that would not be predicted for nonflood flows. Our findings highlight the potential for different magnitude flows to promote not only different amounts, but also different patterns of bedrock erosion, with implications for the role of prehistoric megafloods in the topographic evolution of the eastern Himalaya. Key Points: We simulate a large historical landslide‐dam outburst flood using 2‐D shallow water equations over 400 km through rugged Himalayan topography GeoClaw simulations are consistent with field and remote observations of high‐water marks, deposits, landslides, and reported peak discharge Results improve hazard prediction and understanding of bedrock incision, sediment transport, and deposition during outburst floods